Degradation of coral reefs altered the community trophic structure and reduced the shoaling size of fish - Huang, Mingpan; Wei, Shichao; Li, Qian; Gao, Kuo; Peng, Zhaojie; Chen, Yiting; Zhou, Wenliang; Wei, Fuwen (Frontiers in Conservation Science, 2023)
Coral reefs are among the most productive and diverse ecosystems on the planet, yet have suffered sharp declines in the past few decades. To better understand how reef fish communities respond to disturbances in the South China Sea, we investigated the species diversity, trophic composition, and shoaling size of fish communities of four coral reefs in different states of degradations. We found that reef degradation was related to the dominance of herbivores and the decline of planktivores, reflecting the shift towards an algae-dominant community causing by reef degradation.Additionally, degradation reduced the shoaling size of planktivores, but herbivores and omnivores might benefit from the degradation and formed larger groups in Yongle Reef.Our results shed light on the response of the reef fish community to habitat degradation and provided new insights into the conservation of coral reefs in the South China Sea.